Employing Mary Whitebird’s Short Story Ta-Na-E-Ka to Raise Student’s Ecological Awareness - Ririn Kurnia Trisnawati (Humaniora, 2014)
This paper proposes Mary Whitebird’s Ta-Na-E-Ka to be used as the teaching material to raise students’ ecological awareness based on the research conducted in the English Department, Jenderal Soedirman University, Purwokerto, Indonesia. This is because literature is believed to represent authentic social, political, ecological, and historical events from a particular range of periods, so literature can be employed as authentic teaching material to teach both the language and culture embedded in it. In this particular study, Mary Whitebird’s Ta-Na-E-Ka was chosen because it offers a distinct ecological theme. The literary theory exercised is Ecocriticism, i.e. the study of the relationship between literature and the physical environment; it celebrates nature, the life force, and the wilderness told in the story. This qualitative study employs the data gained from the readers’ questionnaire. It successfully probes the readers’ understanding of the elements of the story, e.g., characters and characterization and theme; it also shows that students are able to capture the issue of nature, physical environment and their relationship with the Kaws as it is proposed by ecocriticism. Therefore, the readers, who are students, become the ecocritics; they are more caring to the world and its nature. In other words, their ecological awareness has sharpened eventually, and Mary Whitebird’s Ta-Na-E-Ka has been successfully used both as the teaching material and as the authentic material to understand the ecocentric value narrated in the story.